Chapter 1 EU's perspective on the functioning of giant online platforms in the digital economy - Ambroziak, Adam A. (Taylor & Francis, 2022)
In the study, the EU's digital market in light of the new regulation issued by the European Commission: the Digital Market Act has been examined. It will allow regulation of a significant part of the EU digital market activities of giant tech companies to the extent that they will be much more complex and restrictive in comparison to the creation of the traditional internal market in the early 1990s. In view of recent changes occurring in the digital market, including the increased expansion of the biggest companies and problems related to competition, the aim of this study is to capture the change in approach of the EU competition policy to entities, so-called gatekeepers, who offer core online platform services as compared to the existing solutions functioning in the traditional European Single Market.